Is there a value of dual-energy X-ray absorptiometry in predicting the histopathologic severity of non-alcoholic steatohepatitis? - Yalniz, M; Ataseven, H; Bahcecioglu, IH; Ozercan, IH (Elsevier Science Bv, 2003)
[Abstract Not Available]
38th Annual Meeting of the European-Association-for-the-Study-of-the-Liver -- MAR 29-APR 01, 2003 -- ISTANBUL, TURKEY